2009
DOI: 10.3109/02713680903283169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening ofRhodopsinandPeripherin/RDSGenes in Mexican Families with Autosomal Dominant Retinitis Pigmentosa

Abstract: Our study adds to the mutational spectrum of adRP by identifying two novel RHO mutations. RHO mutations were responsible of 17% of AD RP Mexican cases, a figure slightly lower to that found in other ethnic groups. Peripherin/RDS mutations are apparently an uncommon cause of AD RP in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…Multiplex ligation-dependent probe amplification was normal, excluding a copy-number variant on the second allele as an explanation for the phenotype (Supplementary Figure S2 online). An F45L substitution has been reported to be pathogenic in ADRP patients, [29][30][31] however, the pathogenic mechanism could not be identified. 10 Bioinformatic analyses were inconclusive; the residue at site 45 is invariant across vertebrates (Supplementary Figure S1 online) and is found on the outer surface of the first TMD (Figure 2a and Supplementary Figure S3 online), but the Grantham score predicts that the effect of the F45L substitution should be minimal ( Table 2).…”
Section: Validation Of Functional Analysesmentioning
confidence: 99%
“…Multiplex ligation-dependent probe amplification was normal, excluding a copy-number variant on the second allele as an explanation for the phenotype (Supplementary Figure S2 online). An F45L substitution has been reported to be pathogenic in ADRP patients, [29][30][31] however, the pathogenic mechanism could not be identified. 10 Bioinformatic analyses were inconclusive; the residue at site 45 is invariant across vertebrates (Supplementary Figure S1 online) and is found on the outer surface of the first TMD (Figure 2a and Supplementary Figure S3 online), but the Grantham score predicts that the effect of the F45L substitution should be minimal ( Table 2).…”
Section: Validation Of Functional Analysesmentioning
confidence: 99%
“…Hence, we focused on the quantitative comparison of ERG responses. Ruther et al (11) and Matias-Florentino et al (59) have reported cases of 30-and 36-year-old S186W-affected patients, respectively, who had either barely recordable or completely abolished ERGs. However, Fishman et al (74) reported that D190N-affected patients at ages of 36 and 80 years had ERGs with delayed but still detectable responses.…”
Section: Thermal Stability Of Rhodopsin and Progression Of Rpmentioning
confidence: 99%
“…Experiments on the nonpathogenic S186A mutation revealed that it increases the rate of thermal decay by 3-fold compared with wild type (WT) (46) and increases the rates of thermal isomerization and hydrolysis of SB by 2 orders of magnitude at 55°C (43,44). However, the pathogenic S186W mutant has not been characterized at the molecular level, although clinical studies suggest a severe phenotype (11,59).…”
mentioning
confidence: 99%
“…Davies and colleagues provided a good example of this in 2012, when they analyzed rod opsin variants using a combination of Sanger sequencing, NGS, genetic and bioinformatics analyses, and functional assays [46,47]. This study demonstrated that some previously reported mutations, such as Phe45Leu [62][63][64], showed an unclear prediction of pathogenicity, but did not appear to have a dysfunctional phenotype. By contrast, a Met39Arg substitution, which was not highly predicted to be pathogenic using bioinformatics analyses, clearly showed trafficking and functional defects (Figure 3) [46,47].…”
Section: Variants Of Unknown Significance Incidental Findings and Bioimentioning
confidence: 88%